(3GdfUjMI GdLGeYI hGdMLI GdbGWYIs - (3YHO GdQMje Hf GdMSf Hf Ydj GdESfhj GdTGaYj, CHh eMeO, LeGd GdOjf,J (B772 (3g` s
(3ChdgG (B:s
(3hHYO aEf Gddg JYGdi bO bGd(B:" (3hEPG CNP Gddg ejKGb GdPjf ChJh GdcJGH djHjfg ddfGS hdGjcJehfg(B" s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde(B:"(3GdOjf GdfUjMI bdfG def jGQShd Gddg bGd ddg hdcJGHg hdQShdg hdGFeI GdeSdejf hYGeJge hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B119 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B203s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B653s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY (B318) s
Keywords: (3GdJhMjO hGdedd hGdfMds